Efficacy, safety and cost-effectiveness of obinutuzumab in patients with follicular lymphoma: a rapid review - Chao Wang; Yunzhuo Dong; Peng Men; Ruixia Zhang; Ying Xiao; Yishan Bu; Yinpeng Qin; Xinran Zhang; Qianqian Dou; Yiheng Yang; Huier Gao; Yi Zhang (Frontiers in Pharmacology)
BackgroundObinutuzumab was approved in China in June 2021 used in combination with chemotherapy (followed by obinutuzumab maintenance) for the treatment of adult patients with previously untreated stage II bulky, III, or IV follicular lymphoma (FL). The clinical application of obinutuzumab has recently begun in China, but there is a lack of evidence to determine under which circumstances it should be considered the treatment of choice. A comprehensive assessment is necessary to evaluate the efficacy, safety, and cost-effectiveness of obinutuzumab in adult patients with FL.ObjectiveTo summarize the evidence on the efficacy, safety, and cost-effectiveness of obinutuzumab in adult patients with FL, aiming to provide medical professionals with evidence for informed choices in clinical practice.MethodsThe approach to this evidence synthesis was a rapid review of systematic reviews/meta-analyses (SR/meta-analyses), health technology assessment (HTA) reports, and pharmacoeconomic studies that brings together and summarizes the efficacy, safety, and cost-effectiveness of obinutuzumab in adult patients with FL. A literature search was conducted across multiple databases, including PubMed, Embase, Wanfang, CNKI, Weipu database, the Cochrane Library, the Centre for Reviews and Dissemination (CRD) database, International Network of Agencies for Health Technology Assessment (INAHTA) and Canada’s Drug Agency (CDA-AMC), International Society for Pharmacoeconomics and Outcomes Research (ISPOR), National Institute For Health and Care Excellence (NICE), Institute For Clinical And Economic Review (ICER), Grey Literature Database and Grey Net International. The studies on obinutuzumab for FL were searched in full text with obinutuzumab, systematic review, meta-analysis, economics, cost, and health technology assessment as keywords, with a search time frame from the date of database creation to 29 November 2024. The literature was screened based on predefined inclusion and exclusion criteria, and data were meticulously extracted and synthesized by two authors. Simultaneously, the quality of the literature was thoroughly assessed.ResultsObinutuzumab based chemotherapy (the chemotherapy regimen-cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP); cyclophosphamide, vincristine, and prednisone (CVP); or bendamustine) significantly prolonged progression free survival (PFS) compared to other chemotherapy regimen at primary and updated analyses. The incidence of grade 3–5 AEs, infusion-related reactions (IRRs), and infection were higher in the obinutuzumab based chemotherapy group compared to other chemotherapies. The economic researches conducted in China, United States, Japan, Italy and Norway had demonstrated that obinutuzumab-based chemothrepy was cost-effective compared to other chemothrepies. Although obinutuzumab significantly prolonged PFS and was cost-effective, its safety profile was considered lower.ConclusionCompared with other chemothrapy regimen, obinutuzumab based chemotherapy significantly prolonged PFS and was cost-effective, while its safety profile was considered lower. Therefore, medical professionals should be caution when using or introducing obinutuzumab treatment for FL patients.